Pengaruh Produk Domestik Bruto, Tingkat Suku Bunga Tabungan Bank Konvensional dan Nisbah Bagi Hasil Terhadap Jumlah Tabungan Mudharabah - Ghina Fauziyyah Umami; Fatmi Hadiani; Radia Purbayati (Journal of Applied Islamic Economics and Finance, 2021)
This study aims to utilize the potential funding sources through mudharabah savings by analyzing several factors that are thought to affect the amount of mudharabah savings. The research method used in this study is a quantitative approach by using multiple linear regression analysis as an analysis method and SPSS 25.0 as analysis tool. The resultsnof the researchnare variablesnof Gross Domestic Product (PDB) and Savings Interest Rate of Conventional Banks (SBT) have significant effect on the amount of mudharabah savings. Partially, PDB has positive effect while SBT has negative effect. On the other side, variable of Profit Sharing Ratio (NBH) has no significant effect on the amount of mudharabah savings. All of three independent variables simultaneously affected the amount of mudharabah savings in BSM.